243 PROGNOSTIC IMPACT OF CXCR7 AND CXCL12 EXPRESSION IN PATIENTS WITH ESOPHAGEAL ADENOCARCINOMA. (17th September 2021) - Goto, Masakazu; Shibahara, Yukiko; Baciu, Cristina; Allison, Frances; Derouet, Mathieu; Yeung, Jonathan; Darling, Gail; Liu, Mingyao
Abstract:  : Chemokines are major regulators of cell trafficking and adhesion. The chemokine CXCL12 and its receptors, CXCR4 and CXCR7, have recently been reported as biomarkers in various cancers, including esophageal squamous cell carcinoma; however, there are few studies of these chemokines in esophageal adenocarcinoma (EAC). In this study, we investigated the relationship between expression of CXCL12, CXCR4 and CXCR7, and prognosis in patients with EAC. Methods: This study examined 55 patients with EAC who were treated in Toronto General Hospital from 2001 to 2010. Tissue microarray immunohistochemistry was used to evaluate the expression of CXCL12, CXCR4 and CXCR7. Evaluation of immunohistochemistry was performed by a pathologist without knowledge of patients' information and scored based on a semiquantitative scoring system. The average score from multiple cancer tissues on the microarray was utilized and patients were divided into high or low expression groups using the median score as a cutoff point. These results were compared with the patients' clinicopathological features and survival. Results: The score of CXCR7 was positively correlated with that of CXCL12 (r = 0.3154). High CXCR7 expression was significantly associated with lymphatic invasion (present vs absent, P = 0.005), higher number of lymph node metastases (pN0–1 vs pN2–3, P = 0.0014) and TNM stage (Stage I-II vs III-IV, P = 0.0168). Patients with high CXCR7 (n = 23) expression was associated with worse overall (OS) and disease-free survival (DFS) (P = 0.0221, 0.0090, respectively), and patients with high CXCL12 (n = 24) tended to have worse OS and DFS (P = 0.1091, 0.1477, respectively). High expression of both CXCR7 and CXCL12 was an independent prognostic factor for DFS on multivariable analysis (HR0.3, 95%CI: 0.1–0.8, P = 0.0115). Conclusion: High CXCR7 expression was associated with poor prognosis in patients with EAC, and high expression of CXCR7 and its ligand CXCL12, had a stronger association on prognosis. Further study of this potential biomarker using whole tissue samples and larger sample size is warranted.